Boom and bust in Bronze Age Britain : the Great Orme copper mine and European trade - Williams, R. Alan (Archaeopress Archaeology, 2023)
About the Author ; Acknowledgements ; Chapter 1: Introduction ; Chapter 2: The Bronze Age research context ; Chapter 3: Bronze Age mining and smelting ; Chapter 4: Great Orme mine site and Pentrwyn smelting site ; Chapter 5: Review of metal characterisation and provenance techniques ; Chapter 6: Methodology, materials and analytical methods ; Chapter 7: Results: Defining the Great Orme mine-based metal group ; Chapter 8: Results: Great Orme ore mineralogy and Pentrwyn slag studies ; Chapter 9: Discussion and interpretation ; Chapter 10: Conclusions and future work ; Bibliography ; Appendix I: Compilation of published chemical analyses of ores from the British and Irish Bronze Age copper mines ; Appendix II: Compilation of Cornish copper ore analyses ; Appendix III: Histograms and correlation coefficients on the chemical analyses of Great Orme copper ores ; Appendix IV: Chemical analyses of Group I palstaves (extracted from OXSAM database) ; Appendix V: Compilation of published lead isotope analyses from the British and Irish Bronze Age copper mines not included in Table 7.11 ; Index.